2018
DOI: 10.1007/s11356-018-3676-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of occupational exposure to pesticide mixtures with endocrine-disrupting activity

Abstract: Occupational exposure to pesticide mixtures comprising active substance(s) and/or co-formulant(s) with known/possible endocrine disrupting activity was assessed using long-term activity records for 50 professional operators representing arable and orchard cropping systems in Greece, Lithuania, and the UK. Exposure was estimated using the harmonised Agricultural Operator Exposure Model, and risk was quantified as a point of departure index (PODI) using the lowest no observed (adverse) effect level. Use of subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…21,26 Some studies to predict pesticide exposure using the Agricultural Operator Exposure Model (AOEM) on formulators and sprayers has been shown that more than 50% of respondents have exceeded the Acceptable Operator Exposure Level (AOEL) for daily exposure, this caused increased health risks due to accumulation of active ingredients of pesticides, especially organophosphate pesticides. 27,28 This study found that the exposed pesticides respondent had a mean level of serum TSH significantly higher than the nonexposed respondent. In contrast, the mean level of serum T 3 and T 4 was significantly lower in exposed respondents, as shown in Table 1.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…21,26 Some studies to predict pesticide exposure using the Agricultural Operator Exposure Model (AOEM) on formulators and sprayers has been shown that more than 50% of respondents have exceeded the Acceptable Operator Exposure Level (AOEL) for daily exposure, this caused increased health risks due to accumulation of active ingredients of pesticides, especially organophosphate pesticides. 27,28 This study found that the exposed pesticides respondent had a mean level of serum TSH significantly higher than the nonexposed respondent. In contrast, the mean level of serum T 3 and T 4 was significantly lower in exposed respondents, as shown in Table 1.…”
Section: Discussionmentioning
confidence: 72%
“…Some studies previously documented in pesticides sprayer and farmers that certain herbicides, fungicides, and insecticides are thyroid disruptors, which had different impacts on the rest of the population. [28][29][30] This study controlled several variables that could affect serum thyroid hormone levels, such as iodine tablet consumption and a history of chronic disease. It could be ascertained that differences in serum levels of thyroid hormone between the two groups are indeed caused by exposure to pesticides.…”
Section: Discussionmentioning
confidence: 99%
“…focused on the comparison of physiological responses of i.a. human hepatoma cells to the pesticide active substance, the pesticide formulation and the major co-formulant (Kaisarevic, Tenji et al 2019) or on the occupational exposure to pesticide formulations with endocrinedisrupting activity comprising the simultaneous exposure to co-formulants and pesticide active substances (Wong, Garthwaite et al 2018). Moreover, the BfR investigates the qualitative and quantitative impact on the uptake and elimination of active substances as influenced by co-formulants in several in vitro studies (Karaca, Fischer et al 2021).…”
Section: Research Activities and Data On Co-formulantsmentioning
confidence: 99%
“…The number of EDCs has markedly increased over the past 60 years. Humans are constantly exposed to hundreds of EDCs mainly through air, water, and food [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%